International arbitration issues, perspectives and practice : liber amicorum Neil Kaplan - Kaplan, Neil (Wolters Kluwer, 2019)
'International Arbitration: Issues, Perspectives and Practice' is a three-part compendium of contributions annotated to reflect Neil Kaplan's over 40-year career as a Judge of the Supreme Court of Hong Kong. Neil is widely referred to as the 'father of arbitration in Hong Kong' who has gone on to become one of the members of the upper echelons of the 'great and the good' of international arbitration. On the occasion of his 75th birthday, Neil Kaplan's unparalleled influence in the field of international arbitration is celebrated in this book which comprises contributions from over twenty-five renowned international arbitration practitioners, all of whom credit Kaplan as having impacted the development of arbitration in their respective jurisdictions or professionally.